Progress of Single-Cell RNA Sequencing Technology in Myocardial Infarction Research - Li, Lanfang; Wang, Min; Ma, Qiuxiao; Li, Yunxiu; Ye, Jingxue; Sun, Xiaobo; Sun, Guibo (Frontiers in Cardiovascular Medicine, 2022)
After myocardial infarction, the heart enters a remodeling and repair phase that involves myocardial cell damage, inflammatory response, fibroblast activation, and, ultimately, angiogenesis. In this process, the proportions and functions of cardiomyocytes, immune cells, fibroblasts, endothelial cells, and other cells change. Identification of the potential differences in gene expression among cell types and/or transcriptome heterogeneity among cells of the same type greatly contribute to understanding the cellular changes that occur in heart and disease conditions. Recent advent of the single-cell transcriptome sequencing technology has facilitated the exploration of single cell diversity as well as comprehensive elucidation of the natural history and molecular mechanisms of myocardial infarction. In this manner, novel putative therapeutic targets for myocardial infarction treatment may be detected and clinically applied.